The degree of secondary school teachers’ possession of twenty-first century skills (a field study in the city of Lattakia) (Journal of Hama University, 2026)
The study aimed to reveal the degree of secondary school teachers’ possession of twenty-first century skills in the city of Lattakia .  The sample was selected using a simple random method and its number was (186) male and female teachers. A study tool was developed, which was a questionnaire. It consisted in its initial form of (25) items covering two areas (innovation and creativity skills, information, media and technology skills). The most prominent results were that innovation and creativity skills came in first place with a percentage of (81.56%), followed by information, media and technology skills with a percentage of (80.84%), and there were no differences attributed to the gender variable, while differences were found in favor of teachers with more than 10 years of experience, followed by teachers from 5 to 10 years, then teachers less than 5 years; with less than 5 years of experience; that is, teachers with more than 10 higher level of 21st century skills than teachers with 10 years of experience or less .                                                                                                                                                  Keywords: Twenty-first century skills, secondary school.
Keywords: Keywords: Twenty-first century skills, secondary school.